On the growth behavior of multiple whiskers generated on Sn/Cu plating −Predicting the growth behavior of the longest whiskers using whisker length distributions - Y. Sakamoto; S. Ishihara; K. Masuda; W. Yamazaki; M. Shimura (Journal of Materials Research and Technology)
Although several studies have examined whisker growth on Sn/Cu plating, research on whisker growth laws remain limited, particularly regarding the collective growth characteristics of multiple whiskers on plated surfaces. In this study, tin-plated copper (Sn/Cu) samples were prepared and used to observe the generation and growth characteristics of numerous whiskers, which are known to grow on Sn-plated surfaces over a long time (380 days). Moreover, the statistical distribution of the lengths of multiple whiskers occurring on the sample surfaces over a certain period (hereafter referred to as whisker length distribution) was focused on. The whisker length distribution was approximated using a three-parameter Weibull distribution. The whisker growth rate (dlw/dt) could be quantitatively evaluated by focusing on the change in the whisker length distribution over time. The growth behavior of the longest whiskers, which pose the highest risk, was assessed by examining lw at F(lw) = 99.9 %, while the growth of whiskers with average length was characterized using lw at F(α) = 63.2 %. Based on the experimental observations and chemical reaction kinetics, a whisker growth law and a growth rate equation were defined. Good agreement was observed between the whisker growth law and the experimental results.